Sharing Economy as Innovative Paradigm Towards Sustainable Development: A Conceptual Review - Pu, Ruihui; Pathranarakul, Pairote (Journal of Reviews on Global Economics, 2019)
Sharing economy has been widely described by scholars as diverse phases towards sustainable development concerning its concept, functions, and goals in recent studies. Historically, the concept of "new capitalism" has been aroused the widespread concerns by scholars when defining the concept of sharing behavior of idle resources back to the year 1961. Moreover, scholars considered further the theoretical perspectives of sharing economy from the year 1978 to 2005. And many scholars started conducting the empirical analysis with the impact of sharing economy on specific industries such as tourism, hotel, mobility and financing sectors by the year 2010. However, there were still only a few scholars studied the field of sustainable development of sharing economy particularly in the mobility sectors and potential implication addressed the implementation of governing policies regarding case of the Chinese government. This article is first to review the previous studies on overall development of sharing economy in current situation, conceptualizing and providing the new sustainable model of sharing economy (particularly in sharing Mobility), led to further address the sharing economy in which regarded such an innovative paradigm towards sustainable development concerning with reviews and empirical studies conducted by previous scholars. Significantly, this study provided significant references to the stakeholders (operators), consumers (users), and administering (Chinese government) the sharing platform such potential issue, bringing the government concerned. Theoretically, it also provides such a new research direction with the sustainable model of sharing economy and potential regulating issues for the future research.